2014
DOI: 10.1108/pr-03-2013-0052
|View full text |Cite
|
Sign up to set email alerts
|

Getting inside the black box

Abstract: Purpose – The purpose of this paper is to explore, and eventually unlocking, the “black box” problem by addressing the potential mediating role of human capital and organizational commitment in the relationship between high performance work systems (HPWS) and perceived firm performance in the Tunisian financial industry. Design/methodology/approach – Based on the strategic human resource management (SHRM) theory, the authors developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 99 publications
(122 reference statements)
3
14
0
1
Order By: Relevance
“…Recurrent performance appraisal for various HR management purposes (Murphy and Cleveland, 1995;Rynes et al, 2005) and associated feedback which has a developmental purpose delivered in an informational manner would improve employee creativity, given the fact that such kind of appraisal avails the employees of areas of improvements in terms of their domain-relevant skills (Shalley and Perry-Smith, 2001;Zhou and Oldham, 2001). Generally, the findings of this research corroborate some of the existing literature such as Ismail et al (2018), Ismail et al (2015; Mansour et al (2014) and Werner (2011). For instance, Ismail et al (2015) study signifies that employee creativity play a mediating role in the relationship between HPWS and performance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Recurrent performance appraisal for various HR management purposes (Murphy and Cleveland, 1995;Rynes et al, 2005) and associated feedback which has a developmental purpose delivered in an informational manner would improve employee creativity, given the fact that such kind of appraisal avails the employees of areas of improvements in terms of their domain-relevant skills (Shalley and Perry-Smith, 2001;Zhou and Oldham, 2001). Generally, the findings of this research corroborate some of the existing literature such as Ismail et al (2018), Ismail et al (2015; Mansour et al (2014) and Werner (2011). For instance, Ismail et al (2015) study signifies that employee creativity play a mediating role in the relationship between HPWS and performance.…”
Section: Discussionsupporting
confidence: 82%
“…Good strategy gives rise to competitive advantage of an organisation over another, and it is connected with the improvement in industrial competencies, productivity and performances of such organisation. Such feat cannot just come about except through the instrumentality of employees who are equipped with the required skills, knowledge and competencies needed for the execution of organisational strategy and planning (Fu, 2013;Ismail, 2014;Ismail et al, 2015;Mansour et al, 2014). HPWS formed a part of numerous resources which give rise to sustainable competitive advantages for the organisations, and consequently enhance organisational performance (Choi, 2014;Choi and Lee, 2013;Chuang and Liao, 2010;Demirbag et al, 2014;Fan et al, 2014;Fu, 2013;Shin and Konrad, 2014;Seidu, 2011).…”
Section: Linking Hpws To Non-financial Firm Performancementioning
confidence: 99%
“…Notably, Khan et al, [88] concluded that a higher employee commitment emerged as a predictor of better performance, considering the public sector of oil and gas in Pakistan. Other studies by Bakiev [89] and Mansour et al, [90] revealed the positive influence of organizational commitment on perceived performance among police officers in Krygyzistan and human resource management (HRM) practices in the Tunisian financial services industry, respectively. Especially regarding the public sector, Camilleri and van der Heijden [91] reported the same result.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, most prior research on HPWS shows a direct and positive relationship with performance. However, the process (mediating actors) through which HPWS affect organizational outcomes has yet to be addressed in an effective way (Mansour et al , 2014; Mihail and Kloutsiniotis, 2016) and demands more attention (Huselid and Becker, 2011; Jiang et al , 2013; Fu et al , 2017). Second, existing research almost exclusively takes a managerial perspective on the relationship between HR and performance, implicitly assuming that managers’ opinions are consistent with employees’ perceptions (Jiang et al , 2013).…”
Section: Introductionmentioning
confidence: 99%